Red Ellen : the life of Ellen Wilkinson, socialist, feminist, internationalist - Beers, Laura, 1978- (Harvard University Press, 2016)
In 1908 Ellen Wilkinson, a fiery adolescent from a working-class family in Manchester, was "the only girl who talks in school debates." By midcentury, Wilkinson had helped found Britain's Communist Party, earned a seat in Parliament, and become a renowned advocate for the poor and dispossessed at home and abroad. She was one of the first female delegates to the United Nations, and she played a central role in Britain's postwar Labour government. In Laura Beers's account of Wilkinson's remarkable life, we have a richly detailed portrait of a time when Left-leaning British men and women from a range of backgrounds sought to reshape domestic, imperial, and international affairs. Wilkinson is best remembered as the leader of the Jarrow Crusade, the 300-mile march of two hundred unemployed shipwrights and steel workers to petition the British government for assistance. But this was just one small part of Red Ellen's larger transnational fight for social justice. She was involved in a range of campaigns, from the quest for official recognition of the Spanish Republican government, to the fight for Indian independence, to the effort to smuggle Jewish refugees out of Germany. During Wilkinson's lifetime, many British radicals viewed themselves as members of an international socialist community, and some, like her, became involved in socialist, feminist, and pacifist movements that spanned the globe. By focusing on the extent to which Wilkinson's activism transcended Britain's borders, Red Ellen adjusts our perception of the British Left in the early twentieth century.--